Theoretical Approaches to Research on Modernization of Russia under Conditions of Complex Society - N. N. Zarubina (Vestnik MGIMO-Universiteta)
The article analyzes the advantages and disadvantages of postmodernism as a sociological approach to the study of the modernization of a complex society. There are discussed the postmodernist approaches to the problems of epistemology, determinism and representation that influence on the understanding of social-economic reality in the works of modern sociologists.